English E-Book as Supporting Learning Media for X Grade Students - Iin Baroroh Ma’arif; Ade Bonita Putri (LPPM Universitas KH. A. Wahab Hasbullah, 2022)
The objective of this research is to develop an English E-book as supporting learning media for students at X grade. This learning media consist of some materials in which each materials are completed by some exercises and quiz. The materials in this E-Book are based on senior high school syllabus of curriculum K13. This is a developmental research which adopt Developmental model in research procedures. This model have several steps, those are; 1) Analysis, 2) Design, 3) Development, 4) Implementation, and 5) Evaluation. The result of this research showed from the media validation result got 4,4 score it was in “very good” category, and the material validation got 4,5 score it was in “very good” category. By having those result, this English E-Book is feasible to be used as supporting learning media for X grade students. Furthermore the result of this research can be used as reference for other researchers in exploring and developing English learning media in different level of students.